2018
DOI: 10.4269/ajtmh.17-1020
|View full text |Cite
|
Sign up to set email alerts
|

Seizures as a Complication of Congenital Zika Syndrome in Early Infancy

Abstract: transmission in Brazil was linked to a large outbreak of microcephaly but less is known about longer term anthropometric and neurological outcomes. We studied a cohort of infants born between October 31, 2015, and January 9, 2016, in a state maternity hospital, followed up for 101 ± 28 days by home visits. Microcephaly (< 2 standard deviations, Intergrowth standard) occurred in 62 of 412 (15%) births. Congenital Zika syndrome (CZS) was diagnosed in 29 patients. Among CZS patients, we observed a significant gai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(49 citation statements)
references
References 8 publications
3
46
0
Order By: Relevance
“…With regard to the age groups, we hypothesized that a significant proportion of participants would present with early seizures in the first 2 months of life and develop an epileptic encephalopathy in the neonatal period, because lissencephaly, a common finding in these affected infants, is known to be an important cause of Ohtahara syndrome . Nevertheless, we did not observe any record of this syndrome in this ZIKV‐affected cohort, a finding consistent with previous studies . The largest proportion of epileptic seizures occurred between the third and ninth months of life, with incidence remaining high until the 15th month and very few new cases after this age.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…With regard to the age groups, we hypothesized that a significant proportion of participants would present with early seizures in the first 2 months of life and develop an epileptic encephalopathy in the neonatal period, because lissencephaly, a common finding in these affected infants, is known to be an important cause of Ohtahara syndrome . Nevertheless, we did not observe any record of this syndrome in this ZIKV‐affected cohort, a finding consistent with previous studies . The largest proportion of epileptic seizures occurred between the third and ninth months of life, with incidence remaining high until the 15th month and very few new cases after this age.…”
Section: Discussionsupporting
confidence: 84%
“…At the end of 24 months, nearly three‐quarters of the monitored children had epileptic seizures, an incidence similar to that described in other studies of children with extensive lissencephaly . Other recent studies of microcephaly cases associated with congenital ZIKV infections have reported either similar or lower rates . Two factors may underlie the difference in rates.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…(4347) While this particular type of brain injury could not be detected even with prenatal MRI, it would be expected to correlate with the reported early onset of seizures/epilepsy in human infants, perturbations to later learning and memory development, and potentially even later onset depression and age-related cognitive decline. (4850) A recent study in infant nonhuman primates also correlated ZIKV infection with hippocampal growth arrest, dysfunctional connectivity by functional MRI, and abnormal socioemotional processing. (51) Longitudinal studies are needed to understand the implications of ZIKV-associated injury to neurogenic cells in the fetus or young children and whether this injury might result in a predisposition to learning disorders, developmental delay or mental illness in childhood and adolescence.…”
Section: Broadening Spectrum Of Zikv-associated Fetal Injurymentioning
confidence: 99%